Apical microleakage evaluation of three different root canal Obturation techniques using dye penetration evaluation method (Mustansiria Dental Journal, 2018)
Background and objectives: The aim of root canal obturation in endodontictreatment is to prevent communication between the oral cavity and periapicaltissues. Several techniques had been introduced to achieve complete filling of theroot canal system. It had been noted that more researches are needed to establishstandard techniques of root canal filling, and all the techniques should becompared for filling root canals. The aim of this study was to compare the apicalsealing ability of three different obturation techniques.Methods: Thirty single rooted teeth were collected and randomly divided into threegroups. There were 10 teeth in each group. The teeth were obturated by guttapercha as follows: Groups 1 with Thermafil, Groups 2 with Soft core, and Groups3 with System B. The apical leakage in these groups was evaluated using a dyepenetration method.Results: The lowest mean rank of leakage was observed for system B and the highestwas observed for the thermafil groups. The difference between Thermafil, softcore and system B was statistically not significant by using Kruskal Wallis test.Conclusion: System B obturation technique show less microleakage than soft coreand thermafil techniques although the differences was not significant.